2004
DOI: 10.1002/chin.200440139
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective, Sulfamide‐Based Human β3‐Adrenergic Receptor Agonists.

Abstract: Potent and Selective, Sulfamide-Based Human β 3 -Adrenergic Receptor Agonists. -[design, synthesis and evaluation of biological activity of a novel series of highly potent and selective β3-AR agonists such as (VII) and (XIII)]. -(DOW*, R. L.; PAIGHT, E. S.; SCHNEIDER, S. R.; HADCOCK, J. R.; HARGROVE, D. M.; MARTIN, K. A.; MAURER, T. S.; NARDONE, N. A.; TESS, D. A.; DASILVA-JARDINE, P.; Bioorg. Med. Chem. Lett. 14 (2004) 12, 3235-3240; Cardiovasc. Metab. Dis., Pfizer Global Res. Dev., Groton, CT 06340, USA; Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…This was attributed to be largely due to poor absorption caused by a high molecular weight (MW = 625) and a lipophilic nature (CLogP = 5.3). During human clinical trials (phase II), a single-dose administration of L-796568 (103, 1g) was found to increase lipolysis and energy expenditure (8%) in overweight to obese male subjects [221][222][223]. A novel series of heterocycle-based analogs were recently reported to be the orally bioavailable 3-AR antagonists by the research group at Pfizer.…”
Section: -Adrenergic Receptor Agonistsmentioning
confidence: 98%
“…This was attributed to be largely due to poor absorption caused by a high molecular weight (MW = 625) and a lipophilic nature (CLogP = 5.3). During human clinical trials (phase II), a single-dose administration of L-796568 (103, 1g) was found to increase lipolysis and energy expenditure (8%) in overweight to obese male subjects [221][222][223]. A novel series of heterocycle-based analogs were recently reported to be the orally bioavailable 3-AR antagonists by the research group at Pfizer.…”
Section: -Adrenergic Receptor Agonistsmentioning
confidence: 98%
“…1015 The same researchers made another series of sulfamide-based agonists 465 which are also effective as β 3 -AR agonists. 1016 Oxazole-containing sulfamides such as 466 have been prepared as PPARα agonists. 1017 Simple sulfamides such as R 1 NHSO 2 NHR 2 with long chains which may contain double carbon−carbon bonds are active PPARα agonists.…”
Section: Inorganic Industrial and Analytical Studiesmentioning
confidence: 99%
“…A patent has described the synthesis of sulfamide β 3 -adrenergic receptor (AR) agonists, see Figure . The same researchers made another series of sulfamide-based agonists 465 which are also effective as β 3 -AR agonists …”
Section: Alicyclic Sulfamidesmentioning
confidence: 99%
“…Researchers at Pfizer have developed a series of sulfamide-based human β 3 -AR agonists [49]. cis-3,5-Dimethylmorpholinylsulfamide 27 was found to be a potent β 3 -agonist (EC 50 = 8 nM, IA = 85%) and showed high selectivity against β 1 -and β 2 -ARs (>1300-and >200-fold, respectively).…”
Section: Modification Of Rhsmentioning
confidence: 99%